Mode of delivery preferences, knowledge, and intention to practice exclusive breastfeeding among female undergraduates at Ladoke Akintola University of Technology, Ogbomoso, Oyo State - Akinremi, Tobi I.; Quadri, Jelili A.; Deniran, Igbagboyemi A.; Ogundairo, Yetunde O.; Fasipe, Funke B.; Oyawale, Blessing O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Exclusive breastfeeding and preferred delivery modes are crucial for promoting maternal and child health. Understanding these factors among young women is important for improving future breastfeeding and delivery decisions. This study aimed to assess knowledge and intentions regarding exclusive breastfeeding and delivery mode preferences among female undergraduates of Ladoke Akintola University of Technology, Ogbomoso, Oyo State. Methods: A descriptive cross-sectional study design was employed. A total of 1,000 respondents were selected through simple random sampling. Data were collected using a semi-structured, interviewer-administered questionnaire covering sociodemographic characteristics, knowledge of exclusive breastfeeding and delivery modes, and intentions related to breastfeeding and childbirth. Data were analyzed using the Statistical Product and Service Solutions (SPSS) version 20.0, employing descriptive statistics and chi-square tests to determine associations, with significance set at p<0.05. Results: Most respondents (75.5%) had heard of exclusive breastfeeding, and 51.9% correctly defined it. A high proportion (75.7%) intended to practice exclusive breastfeeding, while 77.7% preferred vaginal delivery over caesarean section. Overall, 66.8% demonstrated good knowledge of exclusive breastfeeding, although 27.9% believed infant formula and breast milk contain equal nutrients. Significant associations (p<0.05) were found between sociodemographic characteristics, knowledge, and intentions regarding exclusive breastfeeding and delivery preferences. Conclusions: Although awareness and intention to practice exclusive breastfeeding were high, misconceptions persist. Strengthening university-based maternal health education and practical learning initiatives is recommended to enhance accurate knowledge and improve reproductive health decisions among young women.